Pengaruh Brand Experience terhadap Brand Loyalty Pengguna Yamaha Nmax melalui Brand Trust dan Brand Satisfaction - Risal, Muhammad; Ramadhani, Mohammad; Arianto, Doni; Dewa, Bayu Fitranda; Yusuf, Akhmad Rifhiyan; Harahap, Burhanuddin (Studi Akuntansi, Keuangan, dan Manajemen, 2024)
Purpose: This study aims to determine the influence of brand experience on brand loyalty among Yamaha NMAX users in Samarinda City, with brand trust and brand satisfaction serving as mediating variables. Methodology: A quantitative descriptive approach was employed to examine an unknown population. A sample of 100 respondents was determined using the Lames Show formula. Data were collected via a Google Form questionnaire and analyzed using SmartPLS version 3.3. Results: The data indicate that brand experience has a positive and strong impact on brand trust. Additionally, brand pleasure positively and strongly influences brand trust. Brand satisfaction also affects brand loyalty. Importantly, the relationship between brand experience and brand loyalty is mediated by both brand satisfaction and trust. Limitations: The study's variables are limited to aspects that enhance consumer understanding and encourage companies to improve their services, thereby maintaining the company's image. The research is confined to the marketing aspect and focuses specifically on consumer behavior related to product choice. Contribution: This research provides a model of purchasing behavior that emphasizes loyalty. It aims to foster consumer interest in a brand, create a memorable impression, and achieve the company’s goal of instilling experiential behavior supported by trust and satisfaction, ultimately leading to increased consumer loyalty.